Needlestick injuries among nurses in Selangor Public Hospital, Malaysia - Yee, Kok Suet; Abdullah, Nor Fadhilah; Khuan, Lee (Asia Pacific Higher Learning, 2023)
Background: Needlestick injuries (NSIs) are one of the greatest risks nurses face. NSIs are associated with an increased risk of diseases that can be transferred through skin exposure, such as Hepatitis B, Hepatitis C, and the human immunodeficiency virus. Certain factors can influence the mechanism and frequency of NSI among nurses. Objective: To determine the factors associated with the frequency and mechanisms of NSIs among nurses at a public hospital in Selangor. Methods: A cross-sectional study was conducted from April to September 2020. A total of 233 nurses were conveniently sampled from a public hospital in Selangor. A questionnaire was distributed to capture data on socio-demographic characteristics, frequency, and mechanisms of NSI. The inferential statistics were conducted using SPSS 22. Results: Of the 233 respondents, the incidence rate of NSI was 23.6%. Most cases of NSI occurred during the morning shift (12.4%), and the most common mechanism of NSIs was the action of recapping needles (6.9%). Factors associated with the NSI were gender, age, ward, and working experience. Conclusion: The prevalence of NSIs is relatively low in this study. However, nurses should still apply universal precautions to prevent NSIs. Several risk factors that influenced the NSI should be highlighted among nurses and nursing management to prevent its incidence.